Trust-Led Social Capital Formation In Rural Livelihood Transformation: Evidence From A Post-Extractive Community in Indonesia - Agnes Ratih Ari; Bernadeta Nefo Eka Wijayanti; Diah Risti Nur Khasanah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Rural communities undergoing post-extractive transitions often face socio-economic disruption due to the loss of extractive livelihoods, limited adaptive capacity, and institutional uncertainty. Although alternative livelihood sectors are widely promoted to support sustainable development, the social processes underlying successful transitions remain poorly understood. This study examines how social capital is constructed during rural transformation, emphasizing trust as the foundation of collective adaptation. Using an interpretive qualitative case study in a post-extractive community in Indonesia, the research explores trust-building through sustained interactions between local actors and external facilitators. The findings reveal that social capital was not a pre-existing community asset but gradually emerged through trust-building processes that generated bonding, bridging, and linking social capital. These relational dynamics strengthened collective action, institutional collaboration, and livelihood diversification. The study reconceptualizes trust as the enabling mechanism through which social capital is formed rather than merely one of its components. By proposing the concept of trust-led social capital formation, this study offers a process-oriented framework for understanding rural transformation and informing socially grounded interventions that support sustainable livelihood transitions